Addressing Racialized Multicultural Discourses in an EAP Textbook: Working Toward a Critical Pedagogies Approach. Issue 1 (3rd December 2014) - Chun, Christian W.
Abstract : Racialized multicultural discourses emerge in the TESOL classroom via textbook representations of immigrant success stories and perceived racial and cultural differences among students. Although liberal multicultural discourses may be well intentioned, these discourses warrant closer examination for the ways in which they can essentialize cultural identities and enact power dynamics of who is defining and who is being defined. Drawing on an ethnographic English for academic purposes (EAP) classroom case study, and with the aim of bridging the gap between critical theories and actual classroom practices, this article explores the approaches an instructor implemented with students in addressing such discourses in an EAP textbook chapter. The article first presents the chapter's passages and then describes how the discourses were initially taken up by the participants. A conversation between the instructor and the author in which the instructor shared a racializing experience is then featured, providing the context for her subsequent approach in which she revisited the reading with students. The author examines the classroom interactions with two questions in mind: How did the instructor's critical pedagogies approach work to mediate the racialized representations in the chapter? Did this approach facilitate more meaningful dialogical engagements enabling the students to develop their academic literacies?